Security and Monitoring System in Motorcycle Using NFC (Near Field Communication) and GPS (Global Positioning System) - Ahmad Saepudin Firdaos (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
Motorcycle security system using NFC and GPS monitoring is designed to maximize the security of motorcycle that has been provided by the manufacturer. This system will send SMS messages (Short Message Service) to the user's mobile phone when the user's motorcycle gets interrupted like a shock or move. The system uses an NFC reader that can read NFC tags, NFC cards, NFC stickers and NFC Smartphone support that is used as a key companion of the motorcycle's ignition key. In previous research the system only sends Latitude and Longitude data in SMS format so that users must manually enter the data into Google map. This system uses GPS as a motorcycle monitoring media users where users can find out where the existence of a motorcycle in the form of a map, the average speed of a motorcycle, limit the area or radius that can be passed by a motorcycle and turn off the motorcycle system from long distance Specific reasons through the applications contained in the user's smartphone. This system uses an internal battery so it will continue to function even if the user's motorcycle is off.